Des concepts aux indicateurs du développement durable: multidimensionnalité et responsabilisation - Gilles Allaire; Thierry Dupeuble (Développement Durable et Territoires)
To deal with «sustainable agriculture» in practical ways needs to set up indicators. But such indicators are quite difficult to find out, due to the multi-scaled and inter-temporal dimensions of external effects of economic activities and especially of agricultural practices. Externalities issues, which are problems characterized by their public nature, have to be defined and sized at different levels: besides the global one (which concerns debates on global public goods) and the local one (how sustainable are private activities), collective and territorial levels are also necessary to set up socially acceptable responses.